Fatal course of a suicidal intoxication with hydrochloric acid - Koschny, Ronald; Herceg, Maria; Stremmel, Wolfgang; Eisenbach, Christoph (Case reports in gastroenterology, 2013)
Suicidal ingestion of undiluted hydrochloric acid is a rare but live-threatening event. We report on the dramatic and fulminant course of a 61-year-old woman who drank 200 ml of 30-33% hydrochloric acid. On admission to our intensive care unit she was alert and oriented with stable vital signs. Gastroscopy demonstrated complete necrosis from the hypopharynx to the pylorus, which was flushed continuously via drainage catheters. At that time point perforation was not evident. Shortly thereafter she developed an acute abdomen and a tension pneumothorax which was decompressed. CT scan demonstrated esophageal and intestinal perforation with massive mediastinal necrosis. On emergency laparostomy she showed complete necrosis of the intestine and stomach. The patient died 10 h after admission from multiorgan failure. The therapeutic options are critically discussed in comparison to previously reported cases in the literature.
Gesehen am 26.03.2021